Non-specific aortoarteritis (NSAA) in children: a prospective observational study. Issue 1 (9th August 2021) - Gupta, Himanshu; Kaur, Navjyot; Saxena, Anita; Jagia, Priya; Kumar, Sanjeev; Gupta, Saurabh Kumar; Sharma, Sanjeev; Kothari, Shyam S; Ramakrishnan, Sivasubramanian
Abstract : Objective: Prospective data on clinical profile, natural history and outcomes of NSAA (non-specific aortoarteritis) in children is limited. We initiated this prospective study to evaluate the short-term and medium-term outcomes of NSAA in children. Design: Prospective observational study. Setting: Tertiary care hospital in India. Patients: We included 28 consecutive children (<15 years) with a diagnosis of NSAA. Main outcome measures: Clinical profile, symptoms, left ventricular ejection fraction (LVEF), the pattern of vessel involvement, complications and markers of disease activity were assessed at the time of diagnosis. All the patients underwent treatment and interventions as per the current guidelines and were followed up for a mean duration of 13.5±6.7 months for disease activity and outcomes. Results: The mean age of the cohort was 10±2.9 years (14 boys). Twenty (71%) patients had hypertension. Half of the children presented with acute decompensated heart failure (ADHF). Only 21 patients (75%) met Sharma et al modified Ishikawa criteria for the diagnosis. The children with active disease (36%) were managed with immunosuppressive drugs. Percutaneous and surgical interventions were performed in 26 (93%) children. New York Heart Association functional class, LVEF and control of hypertension improved in most children on follow-up. Four children developed vascular restenosis requiring reinterventions. There was no death during mid-term follow-up. Conclusions: Children with NSAA, unlike adults seldom present with classical features of the disease. ADHF and ventricular dysfunction are strikingly common in children. Appropriate immunosuppressive therapy for active disease and timely intervention improves clinical outcomes over a medium term follow-up. Future studies assessing long-term outcome are needed.